The Influence of Workload and Job Stress On Work Productivity Through The Work Environment Of Employees At Kpp Pratama Jakarta Mampang Prapatan - Kurniawan, Nanang; Harry Indra Tjahyo; Iwan Kurniawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research aims to: 1) determine the effect of workload on the work environment, 2) determine the effect of work stress on the work environment, 3) determine the effect of workload on work productivity, 4) determine the effect of work stress on work productivity, 5) determine the effect of the environment work on work productivity, 6) know the effect of workload on work productivity through the work environment, and 7) know the effect of work stress on work productivity through the work environment. The research was conducted at the KPP Pratama Jakarta Mampang Prapatan office with a research sample of 108 respondents. The sampling technique uses a saturated sample technique. The data analysis method uses descriptive analysis and path analysis. The research results show that: 1) workload has a positive and significant effect on the work environment, 2) work stress has a positive and significant effect on the work environment, 3) work load has a positive and significant effect on work productivity, 4) work stress has a positive and insignificant effect on work productivity, 5) the work environment has a positive and significant effect on work productivity, 6) there is no positive and significant effect of workload on work productivity through the work environment, and 7) workload has a positive and significant effect on work productivity through the work environment